Advanced MRV to capture mitigation impacts -recent analysis and tools - Wollenberg, Eva Karoline; Wilkes, Andreas (2018)
Authors: Lini Wollenberg (CCAFS, UVM) and Andreas Wilkes (Unique Forestry and Land Use) Presented at workshop: Increasing impact: How to achieve mitigation of greenhouse gas emissions in the dairy sector at large scales 30 August 2018 at Wageningen University and Research